Strengthening Armenian Irrigation Capability through Extension Education and Mentoring - Kevin Heaton; James Barnhill; Robert W. Hill (Journal of International Agricultural and Extension Education, 2012)
The disintegration of the Soviet Union in the early 1990s led to the creation of 440,000 small,privately owned farms in the country of Armenia. Armenian farmers, largely untrained in crop production, needed education and experience in all aspects of agriculture production, including irrigation management. In order to provide irrigation information and resources to individual farmers, the Armenian extension system itself was in need of mentoring by qualified individuals. Utah State University (USU) extension irrigation specialists trained Armenian extension personnel in irrigation fundamentals, implemented a soil moisture monitoring program and conducted on farm irrigation research. Between 2001 and 2005, USU Extension trained Armenian extension specialists and agents in over 25 in country irrigation management workshops. The mentoring team monitored soil water in on farm demonstrations and reduced the number of irrigation water events on many fields through scientific irrigation scheduling. They also conducted impact interviews each fall and found that 54-61% of farmers saved irrigation water and farmers averaged 41-159 USD per hectare in net benefits from the program. Prior to 2003, Armenian flood irrigation management was perceived as “inefficient.”The irrigation specialists conducted 60 in field efficiency evaluations and found that Armenian farmers achieved above average efficiency. This multi year project suggests that education and mentoring efforts improved irrigation management, which in turn could reduce the demand for irrigation water and improve the economic and agricultural sustainability of Armenia.
Keywords: Armenia; Soil Moisture; Irrigation Fundamentals; Irrigation Management; IrrigationEfficiency